The influence of cancer patient characteristics on the recommendation of physical activity by healthcare professionals - Haussmann, Alexander; Ungar, Nadine; Tsiouris, Angeliki; Sieverding, Monika; Wiskemann, Joachim; Steindorf, Karen (International journal of behavioral medicine, 2020)
Although physical activity (PA) is beneficial for patients with cancer, healthcare professionals (HCP) still scarcely recommend it. This study aimed to determine how HCP’ sociodemographic and professional characteristics and their subjective assessments of patient characteristics are associated with their PA recommendations to patients with cancer.